Hubungan Sosiodemografi dan Pengetahuan terhadap Tingkat Kecemasan Pasien Pre Operasi di Instalasi Bedah Sentral Rsud Karawang - Suara, Mahyar; Nanlohi, Yopi (Universitas Malahayati, 2025)
ABSTRACT Preoperative is a stage that begins when there is a decision to perform surgical intervention and ends when the patient is sent to the operating table. Clients who will undergo surgery will show high stress compared to the group of clients who are treated without a surgical plan. When the client arrives in the preoperative room, it is a condition that increases the client's anxiety. The anxiety they experience is usually related to all kinds of foreign procedures that the patient must undergo and also the threat to life safety due to all kinds of surgical procedures and anesthesia. Purpose This study aims to determine the relationship between sociodemographics and knowledge of the level of anxiety of preoperative patients in the Central Surgical Installation of Karawang Hospital. The method of taking research samples used Acidental sampling. This study used a Quantitative research design with a cross-sectional approach. The data collection tool used a questionnaire sheet, data analysis used the Chi-square test. The results of the study obtained data that had low knowledge and mild anxiety were 25 respondents with a percentage of 49.0% and those with moderate knowledge and mild anxiety were 23 respondents with a percentage of 45.1%. Meanwhile, those who experienced severe anxiety and low knowledge were 2 respondents with a percentage of 33.3%. From the results of the Chi-Square Test, a P-Value of 0.034 (0.05) was obtained, meaning that there was a significant relationship between knowledge and the level of pre-operative anxiety in the Central Surgical Installation of Karawang Hospital. The conclusion of this study is that there is a relationship between sociodemographics and knowledge on the level of pre-operative patient anxiety in the Central Surgical Installation of Karawang Hospital. Keywords: Sociodemographics, Knowledge and Anxiety Level ABSTRAK Pre operasi merupakan tahap yang dimulai ketika ada keputusan untuk dilakukan intervensi bedah dan diakhiri ketika pasien dikirim ke meja operasi. klien yang akan dilakukan pembedahan akan menunjukan stress yang tinggi dibandingkan dengan kelompok klien yang dirawat tanpa rencana tindakan pembedahan. Ketika klien tiba di ruangan pre operasi merupakan keadaan yang menambah kecemasan klien. Kecemasan yang mereka alami biasanya terkait dengan segala macam prosedur asing yang harus dijalani pasien dan juga ancaman terhadap keselamatan jiwa akibat segala macam prosedur pelaksanaan operasi dan tindakan pembiusan. Penelitian ini bertujuan untuk mengetahui hubungan sosiodemografi dan pengetahuan terhadap tingkat kecemasan pasien pre operasi di Instalasi bedah sentral RSUD Karawang. Pengambilan sampel penelitian menggunakan Acidental sampling. Penelitian ini menggunakan desain penelitian Kuantitatif dengan pendekatan cross sectional. Alat pengumpulan data menggunakan lembar kuesioner, analisa data menggunakan uji Chi-square. Hasil penelitian didapatkan data yang memiliki pengetahuan rendah dan kecemasan ringan ada 25 responden dengan presentase 49,0% dan yang memiliki pengetahuan sedang dan kecemasan ringan ada 23 responden dengan presentase 45,1%. Sedangkan yang mengalami kecemasan berat dan berpengetahuan redah ada 2 responden dengan presntase 33,3%. Dari hasil Uji Chi-Square diperoleh P-Value 0,034 (0,05), artinya ada hubungan yang signifikan antara penegtahuan dengan tingkat kecemasan pre operasi di Instalasi bedah sentral RSUD Karawang. Kesimpulan dari penelitian ini adalah ada hubungan sosiodemografi dan pengetahuan terhadap tingkat kecemasan pasien pre operasi di Instalasi bedah sentral RSUD Karawang. Kata Kunci: Sosiodemografi, Pengetahuan dan Tingkat Kecemasan